Interventional Treatment for a Choledocho-Colonic Fistula Due to Bile Duct Injury after Laparoscopic Cholecystectomy: A Case Report - Woo Jin Shim; Young Hwan Kim (Journal of the Korean Society of Radiology)
Choledocho-colonic fistula is a rare complication that can occur following laparoscopic cholecystectomy. Although there are a few case reports attempting surgical repairs, including primary closure of the colon enterostomy and hepaticojejunostomy, or endoscopic repair in patients with choledoco-colonic fistula, no interventional treamtnet has been reported so far. Herein, we present a case of bile leak after cholecystectomy due to iatrogenic biliary injury that results in choledocho-colonic fistula, which was successfullytreated by Nbutyl cyanoacrylate embolization.